Synaesthesia lost and found: two cases of person- and music-colour synaesthesia - Mitchell, Kevin (My University, 2017)
Synaesthesia is a developmental condition involving cross-communication between sensory modalities or substreams whereby an inducer (e.g. a sound) automatically evokes a concurrent percept in another modality (e.g. a colour). Whether this condition arises due to atypical structural connectivity (e.g., between normally unconnected cortical areas) or altered neurochemistry remains a central question. We report the exceptional cases of two synaesthetes – subjects AB and CD – both of whom experience coloured auras around individuals, as well as coloured perceptions in response to music. Both subjects have, in recent years, suffered a complete loss or reduction of their synaesthetic experiences, one (AB) through successive head traumas, including a lightning strike, followed by a number of medications, and the other (CD) while taking anxiolytic medications. Using semi-structured interviews and data from the Synaesthesia Battery and a colourpicker task, we characterize the phenomenological characteristics of their pre-loss synaesthesia, as well as the subsequent restoration of each subject's synaesthetic experiences (in the months post-trauma for AB, and after cessation of medication for CD). Even after years of suppression, the patterns of associations were highly consistent with those experienced pre-injury. The phenomenological experience of synaesthesia can, thus, like most conscious experiences, be modulated by pharmacologically diverse medications or head injury. However, the underlying neural substrates mediating specific synaesthetic pairings appear remarkably ‘hard-wired’ and can persist over very long periods even under conditions that alter or completely suppress the conscious synaesthetic experience itself.
Keywords: Synaesthesia; colourpicker task; anxiolytic medications; Aura; Conscious experience; Injury; Pharmacology; Suppression